Mobile application: car ignition system via Bluetooth technology - Johari, Mohd Huzairi (2007)
Mobile application: car ignition system via Bluetooth technology has been develop and implemented. This project consists hardware and software development. For the hardware parts for this project are Rabbit Core Module (RCM 3100) with prototyping board, EmbeddedBlue506 serial module (eb506), bipolar junction transistor as a switch, car alarm remote and auto starter. The software Dynamic C is used to write and load the program into RCM3100. To start using this application, firstly, the unique address of Bluetooth mobiles for specific persons must be set. This was done during in programming process. It is done by load the program into the RCM3100 memory by using dynamic C. Then the system were let in standby and wait for Bluetooth connection. When Rabbit detected trusted Bluetooth signal, the LED on the car remote will turn on twice. Then, the car engine will get started after a few seconds. Auto Starter must be installed to the existing car alarm system to use this application. This system only ignites the car engine by using mobile phone. The car doors are still locked but the engine will keep running. The advantages of this project it can transmit a Bluetooth signal without need a line of sight and less interference. In heavy rain condition the signal are low and sometimes it can not detected the signal.